High spatial and temporal resolution cell manipulation techniques in microchannels. Issue 6 (18th February 2016) - Novo, Pedro; Dell'Aica, Margherita; Janasek, Dirk; Zahedi, René P.
Abstract : Reviewing latest developments on lab on chips for enhanced control of cells' experiments. Abstract : The advent of microfluidics has enabled thorough control of cell manipulation experiments in so called lab on chips. Lab on chips foster the integration of actuation and detection systems, and require minute sample and reagent amounts. Typically employed microfluidic structures have similar dimensions as cells, enabling precise spatial and temporal control of individual cells and their local environments. Several strategies for high spatio-temporal control of cells in microfluidics have been reported in recent years, namely methods relying on careful design of the microfluidic structures ( e.g. pinched flow), by integration of actuators ( e.g. electrodes or magnets for dielectro-, acousto- and magneto-phoresis), or integrations thereof. This review presents the recent developments of cell experiments in microfluidics divided into two parts: an introduction to spatial control of cells in microchannels followed by special emphasis in the high temporal control of cell-stimulus reaction and quenching. In the end, the present state of the art is discussed in line with future perspectives and challenges for translating these devices into routine applications.